Notes On Contemporary Imperialism and Socialism with Chinese Characteristics: The Contribution of Cheng Enfu’s Team (World Marxist Review, 2025)
Imperialism remains a valid concept as the fundamental structures and contradictions of the international system analyzed by Lenin. China has the undeniable merit of showing that socialism is not only economically viable, but also a superior system that will surpass capitalism in the future. The study of Cheng Enfu’s team, in partnership with other authors, offers an excellent contribution on these topics. The aim of this article is to discuss the analysis of Cheng Enfu’s team about imperialism and socialism with Chinese characteristics, essential issues not only for understanding the process of socialist transition in China, but also the impacts of this process on the international system.